THE SIGNIFICANCE OF FINANCIAL LITERACY FOR MUSLIM WOMEN IN MANAGING FAMILY FINANCE - Wan Noor Hazlina Wan Jusoh,; Nor Faezah Ghazi Ahmad,; Muhammad Hamdan Syafieq Ahmad, (Journal of Islamic, Social, Economics and Development, 2022)
modern woman wears multiple hats - from a loving daughter and nurturing wifeto a selfless mother and dedicated employee. On top of meeting her household responsibilitiesand family commitments, she also makes a mark outside and pursues a successful professionallife. And yet, most women seem to be neglecting a very crucial aspect of their life: personalfinances. Generally, women play an important role in managing family finance since financialplanning is essential for financial wellbeing of a family. While on the one hand, the role offinancial planning is largely acknowledged, on the other hand the significance of financialliteracy is still lagging, especially for women. Women consistently score lower than men onfinancial literacy measures, and this gender-based gap may negatively impact not only thefinancial well-being of women themselves but also their families. Thus, this study aims atexplaining the significance of financial literacy for Muslim women in managing family finance.Library research is used to discuss the significance of financial literacy for Muslim women inmanaging family finance and how Islam looks at it. It is found that Muslim women play asignificant role in managing family finance to ensure family wealth management, familywellbeing, and Shari’ah-compliant financial practices.